Dinamika Penggunaan Lahan Kecamatan Temon Sebagai Kawasan Bandara Internasional Yogyakarta - Nurkukuh, Dwi Kunto; Candra Ragil (Institut Teknologi Nasional Yogyakarta, 2023)
Development in Indonesia aims to prosper the people. Infrastructure development such as airports is also hoped to bring prosperity to the community. However, in addition to these positive impacts, there are also negative impacts, namely causing changes in the use of the surrounding land. Yogyakarta is building Yogyakarta International Airport in Temon District, Kulonprogo Regency. Therefore, this study aims to determine the dynamics of land use in Temon District before and after the construction of the Yogyakarta International Airport. The research method uses a qualitative approach with an analysis of the classification of satellite imagery from 2012-2022. The dynamics of land use in 2012-2017 showed the conversion of dry land agriculture to ponds of 260 ha and the conversion of paddy fields to settlements of 14.50 ha. Whereas in 2017-2022 the conversion of dry land agriculture to airports was 329.48 ha, conversion of ponds to airports was 74.06 ha, conversion of paddy fields to airports was 70.06 ha, and residential conversions to airports were 66.73 ha. The most changes in land use in Temon District are dry land agriculture, ponds, rice fields, settlements into airports.